Zum Stand der Ortung und Fangtechnik in der antarktischen Krillfischerei - Steinberg, R.; Mentjes, Tönjes (1978)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010